The Safety and Immunogenicity of GTU®MultiHIV DNA Vaccine Delivered by Transcutaneous and Intramuscular Injection With or Without Electroporation in HIV-1 Positive Subjects on Suppressive ART - Haidari, G.; Day, Suzanne; Wood, M.; Ridgers, H.; Cope, Alethea V.; Fleck, Sue; Yan, Celine; Reijonen, Kalevi; Hannaman, Drew; Spentzou, Aggeliki; Hayes, Peter; Vogt, A.; et al. (Frontiers in Immunology, 2019)
Previous studies have shown targeting different tissues via the transcutaneous (TC) and intramuscular injection (IM) with or without electroporation (EP) has the potential to trigger immune responses to DNA vaccination. The CUTHIVTHER 001 Phase I/II randomized controlled clinical trial was designed to determine whether the mode of DNA vaccination delivery (TC+IM or EP+IM) could influence the quality and function of induced cellular immune responses compared to placebo, in an HIV positive clade B cohort on antiretroviral therapy (ART). The GTU®MultiHIV B DNA vaccine DNA vaccine encoded a MultiHIV B clade fusion protein to target the cellular response. Overall the vaccine and regimens were safe and well tolerated. There were robust pre-vaccination IFN-γ responses with no measurable change following vaccination compared to placebo. However, modest intracellular cytokine staining (ICS) responses were seen in the TC+IM group. A high proportion of individuals demonstrated potent viral inhibition at baseline that was not improved by vaccination. These results show that HIV positive subjects with nadir CD4+ counts ≥250 on suppressive ART display potent levels of cellular immunity and viral inhibition, and that DNA vaccination alone is insufficient to improve such responses. These data suggest that more potent prime-boost vaccination strategies are likely needed to improve pre-existing responses in similar HIV-1 cohorts.